Perlindungan Hukum Bagi Konsumen Terhadap Peredaran Bebas Kosmetik Beretiket Biru - Dewinta, Dewinta (PSHPM Untag Semarang, 2023)
Nowadays, the distribution of cosmetics with blue labels is increasingly widespread. The reason is that some time ago there was an uproar in the news that there was a well-known brand of skincare with a blue label but it was sold in public places such as malls and even grocery stores. The blue label is a label for medicines (specifically external medicines such as ointments, creams, etc.) given by doctors according to the patient's condition. So, skincare with a blue label can only be used by patients who have consulted a doctor, who then prescribes medication to a pharmacist. This research uses a normative juridical approach with descriptive qualitative data analysis. The conclusions of this research include: 1) legal protection for consumers based on the UUPK, namely Article 4 letter a and Article 7 letter d concerning quality standards for goods in Indonesia, 2) the legal consequences of selling cosmetics with blue labels and resulting in consumer losses, will be subject to sanctions through Article 60 Paragraph 2 where a sanction of Rp. 200,000,000 (two hundred million rupiah), then, if there is no good faith in implementing the specified sanctions, the business actor can be sued through the Consumer Dispute Resolution Agency or the courts in their respective regions in accordance with Articles 19 and 45 paragraph 2.